Distribution of mental health professionals working on site in English and Welsh general practices. Issue 6903 (28th August 1993) - Kendrick, T; Sibbald, B; Addington-Hall, J; Brenneman, D; Freeling, P
Abstract : OBJECTIVE--To describe the nature and distribution of mental health professionals working on site in general practices. DESIGN--Postal questionnaire and telephone interview survey. SETTING--English and Welsh general practices. SUBJECTS--1880 general practitioners, of whom 1542 (82%) responded. MAIN OUTCOME MEASURES--Prevalence, types, and distribution of mental health professionals working on site among general practices. Factors predicting the presence of mental health professionals on site. RESULTS--The number of practices reporting the presence on site of each type of professional were 528 for community psychiatric nurses; 266 for practice counsellors; 177 for clinical psychologists; 132 for psychiatrists; 96 for psychiatric social workers; and 45 for psychotherapists. Mental health professionals tended to cluster together in practices more often than expected by chance alone. Practice characteristics which independently predicted the presence of a mental health professional on site were having four or more partners; being a training practice; and running stress, bereavement, or other mental health clinics. The proportions of practices with mental health professionals on site varied significantly among health regions. There was no association between the presence of mental health professionals on site and the location of practices, the social class mix of patients, or the estimated percentage of elderly patients or patients of non-European origin. CONCLUSIONS--Mental health professionals tend to cluster together, with a preponderance in larger training practices. Specialist mental health care provision within general practices is unevenly distributed. Further research is needed to determine whether this uneven distribution reflects differences in need or inequalities in the provision of mental health services.